Divine and human providence philosophical, psychological and theological approaches - Silva, Ignacio Alberto 1978-; Kopf, Simon Maria ca. 21. Jh (Routledge, 2021)
"This volume offers an original perspective on divine providence by examining philosophical, psychological, and theological perspectives on human providence as exhibited in virtuous human behaviours. Divine providence is one of the most pressing issues in analytic theology and philosophy of religion today, especially in view of scientific evidence for a natural world full of indeterminacies and contingencies. Therefore, we need new ways to understand and explain the relations of divine providence and creaturely action. The volume is structured dynamically, going from chapters on human providence to those on divine providence, and back. Drawing on insights from virtue ethics, psychology and cognitive science, the philosophy of providence in the face of contingent events, and the theology of grace, each chapter contributes to an original overall perspective: that human providential action is a resource suited specifically to personal action and hence related to the purported providential action of a personal God. By putting forward a fresh take on divine providence, this book enters new territory on an age-old issue. It will therefore be of great interest to scholars of theology, philosophy, and religion and science"--
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Philosophie; Theologie; Willensfreiheit; Determinismus; Vorsehung; Psychologie; Causation; Determinism (Philosophy); Free will and determinism; Providence and government of God; Aufsatzsammlung